HALAL TOURISM: AN ANALYSIS OF TOURISM POTENTIAL IN TORAJA - Wahyu, A. Rio Makkulau; Anwar, Wirani Aisiyah; Khalik, Muh. Akramul; Salsabila, Putri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research analyzes the potential development of halal tourism or Muslim-friendly in Toraja. The development of halal tourism in Indonesia has shown significant progress, aligned with the increasing number of global Muslim travelers. Indonesia's recognition as a Top Muslim-Friendly Destination in the Global Muslim Travel Index reflects the country's commitment to providing tourism services that are friendly to Muslim travelers. The research methodology employed a desk research approach integrating data collection through analysis of scholarly articles, digital media including news and social media, and literature review to gather data for analysis. The research findings indicate that Toraja as a tourist destination has great potential to be developed as a halal or Muslim-friendly destination. Muslim travelers show high interest in this destination, especially if facilities such as halal food, places of worship, and accommodations compliant with Islamic principles are available. Toraja, with its unique cultural heritage and natural beauty, attracts Muslim travelers, yet the infrastructure supporting halal tourism needs improvement. Collaboration between the government, tourism industry stakeholders, and local communities is crucial to realizing this development. With appropriate strategies, the development of halal tourism in Toraja will not only increase the number of Muslim tourist visits but also promote local economic growth and preserve local culture